Deciphering the Enigmatic Function of Pseudomonas Metallothioneins - Habjanič, Jelena; Mathew, Anugraha; Eberl, Leo; Freisinger, Eva (Frontiers in Microbiology, 2020)
Metallothioneins (MTs) are low molecular weight, Cys-rich proteins that sequester both essential and non-essential metal ions. Despite being highly conserved in the Pseudomonas genus of Gram-negative bacteria, knowledge of their physiological function in this species is scarce. Using the strain P. fluorescens Q2-87 as a model organism, we investigated the role of a conserved MT in zinc homeostasis, cadmium detoxification as well as its implications in stress response. We show that MT expression is only induced in the stationary phase and provides a fitness benefit for long-term starvation survival, while it is not required for metal resistance and acquisition, oxidative or nitrosative stress response, biofilm formation or motility.